Balancing collective responsibility, individual opportunities and risks: a qualitative study on how police officers reason around volunteering in an HIV vaccine trial in Dar es Salaam, Tanzania - Bakari Muhammad; Mwami Joachim; Kohi Thecla W; Thorson Anna; Tarimo Edith AM; Sandström Eric; Kulane Asli (BMC, 2010)
Abstract Background Results from HIV vaccine trials on potential volunteers will contribute to global efforts to develop an HIV vaccine. The purpose of this study among police officers in Dar es Salaam, Tanzania, was to explore the underlying reasons that induce people to enrol in an HIV vaccine trial. Methods We conducted discussions with eight focus groups, containing a total of 66 police officers. The information collected was analyzed using interpretive description. Results The results showed that participants were motivated to participate in the trial by altruism, and that the participants experienced some concerns about their participation. They stated that altruism in the fight against HIV infection was the main reason for enrolling in the trial. However, young participants were seriously concerned about a possible loss of close relationships if they enrolled in the HIV vaccine trial. Both men and women feared the effect of the trial on their reproductive biology, and they feared interference with pregnancy norms. They were unsure about risks such as the risks of acquiring HIV infection and of suffering physical harm, and they were unsure of the intentions of the researchers conducting the trial. Further, enrolling in the trial required medical examination, and this led some participants to fear that unknown diseases would be revealed. Other participants, however, saw an opportunity to obtain free health services. Conclusions We have shown that specific fears are important concerns when recruiting volunteers to an HIV vaccine trial. More knowledge is needed to determine participants' views and to ensure that they understand the conduct of the trial and the reasons it is being carried out.